2014
DOI: 10.1242/jeb.109041
|View full text |Cite
|
Sign up to set email alerts
|

Cold acclimation increases cardiac myofilament function and ventricular pressure generation in trout

Abstract: Reducing temperature below the optimum of most vertebrate hearts impairs contractility and reduces organ function. However, a number of fish species, including the rainbow trout, can seasonally acclimate to low temperature. Such ability requires modification of physiological systems to compensate for the thermodynamic effects of temperature on biological processes. The current study tested the hypothesis that rainbow trout compensate for the direct effect of cold temperature by increasing cardiac contractility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 46 publications
4
48
3
2
Order By: Relevance
“…The fish heart remodels with seasonal temperature change [23, 36, 39, 40, 11, 13, 19, 43, 42, 30]. Here, we focused on the passive properties of the rainbow trout atrium across multiple levels of biological organisation following chronic cooling and warming.…”
Section: Discussionmentioning
confidence: 99%
“…The fish heart remodels with seasonal temperature change [23, 36, 39, 40, 11, 13, 19, 43, 42, 30]. Here, we focused on the passive properties of the rainbow trout atrium across multiple levels of biological organisation following chronic cooling and warming.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that these changes help to compensate for the effects of temperature on the heart's capacity to support the oxygen requirements of the animal. For example, Klaiman et al (2014) demonstrated that the magnitude and rate of ventricular pressure generation was greater in hearts from trout acclimated to 4°C than in those from animals acclimated to 11 or 17°C. In addition, cold acclimation has been demonstrated to cause cardiac hypertrophy and to increase cardiac connective tissue, while warm acclimation causes the opposite response (Keen et al, 2017;Klaiman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These seemingly inconsistent observations must, however, be considered carefully as Farrell et al (1996) investigated the integrated response of in situ perfused heart preparations while our own experiment targeted a single cellular mechanism i.e., intracellular Ca 2+ mobilization. The possibility cannot be excluded that acclimation conditions influence other components of the contractile machinery such as the Ca 2+ sensitivity of force generation, the rate of cardiac actomyosin ATPase or the phosphorylation of cardiac troponins (Klaiman et al 2014), resulting in a different integrated response.…”
Section: Discussionmentioning
confidence: 99%